EVALUATION OF CIPP-BASED CURRICULUM MANAGEMENT IN IMPROVING EDUCATIONAL PERFORMANCE - Muhammad Abdillah Khairi; Muhammad Syam; Inom Nasution (Yayasan Amanah Nur Aman, 2026)
The quality of learning in Indonesia still faces various challenges, such as the mismatch between the curriculum and student needs and limited resources. Curriculum evaluation based on the CIPP (Context, Input, Process, Product) model is considered a comprehensive approach to improving the overall quality of education. This study used a literature review method with qualitative and comparative analysis of various studies on the application of the CIPP model in curriculum evaluation, specifically the Merdeka Curriculum and the 2013 Curriculum. The results show that context evaluation helps adapt the curriculum to the needs of the learning environment, while input evaluation highlights the importance of teacher readiness and supporting facilities. Process evaluation reveals the need for innovation in learning methods for greater effectiveness, and product evaluation shows improved student learning outcomes despite persistent implementation challenges. The CIPP model has proven effective as a holistic and sustainable evaluation tool to support improvements in the quality of learning. Thus, the implementation of CIPP-based curriculum evaluation is highly recommended as a strategy to improve the quality of education systematically and adaptively according to current developments.